Relationship between Family Support with Relapse in Schizophrenic Patients - Aceng Suhermansyah; Gajali Rahman; Badar (PT FORMOSA CENDEKIA GLOBAL, 2023)
According to Afconneri et al's research, (2020), factors that influence relapse in schizophrenic clients include educational status, work status, living with caregivers, level of anxiety, family support, caregiver burden and adherence to taking medication. The support provided by the family can improve the client's recovery or compliance in undergoing therapy at home. The purpose of this study was to analyze the relationship between family support and relapse in schizophrenia patients in the working area of ​​the Labanan and Teluk Bayur Health Centers, Berau District. Shows that the results of the hypothesis test obtained a p value of 0.001, so that there is a relationship between family support and recurrence of schizophrenia patients in the Work Area of ​​the Labanan and Teluk Bayur Health Centers, Berau District.